Cytotoxic Effect of Puya Chilensis Collected in Central Chile - Zuniga-Navarro, G; Contreras-Arredondo, R (SAGE Publications Inc., 2022)
This study sought to evaluate the pharmacological activity of metabolites isolated from the dried and lyophilized ethanol extracts as well as other solvent fractions of the currently endangered Puya chilensis Molina (Chagual) by analyzing their effects on a human hepatocellular carcinoma (HCC) cell line. We identified several active metabolites from Chagual extracts and two, in particular, carnosol, were found in all the prepared fractions. In addition, Chagual exhibited considerable cytotoxicity against the cancer cell line used in this study, with a half-maximal inhibitory concentration (IC50) of 0.44 ± 0.11 and 0.27 ± 0.04 after a 72-hour treatment and, therefore, has the potential for further investigation as a source of candidate therapeutic agents. © The Author(s) 2022.